Las actividades lúdicas y su influencia en el aprendizaje de los Estudiantes de Tercer Grado de Educación Básica de la Unidad Educativa “Chipe Hamburgo” año lectivo 2016- 2017. - Calapaqui Oña, Luis Edwin (2019)
This project consisted of determining the incidence of the play activities in the educational process, through the use and application of innovative methods and techniques. He began with an inquiry to the director, teachers, students and parents, of this institution, on the application, use of concrete materials, technical techniques and the way that significant learning is fostered, for after the analysis of this problem, contribute with alternatives of practical application, for the new educational pedagogy. The theoretical foundations of the investigation are based on the constructivist theory being a descriptive type research; the research design is bibliographic and observation record, the analysis of the results is carried out through the surveys directed to the docents and best students of the same, taking into account that the lack of playful activities affects unfailingly in the educational process of the students. This sense the teacher has the responsibility to enrich their pedagogical practice with innovative and creative techniques, for the student to strengthen their knowledge, hence the importance of promoting the free expression of children through games, dramatizations, songs, poetry and especially playful activities in the use of new learning techniques. Through this research the importance of the game is deepened as a basic strategy within the student's learning and the beneficiaries are the students who improve their knowledge in a creative way.